A case of wound infection caused by Shewanella algae in the south of Iran - M. Taherzadeh; M. Katouli; R. Amirinejad; M.R. Farzaneh; O. Gharibi (New Microbes and New Infections, 2014)
Shewanella algae was isolated from the purulent discharge in the navel area of a young male with a history of swimming in the Persian Gulf. A routine laboratory diagnosis procedure, followed by 16S rRNA gene sequence analyses, was used to avoid misidentification with other species of Shewanella. The bacterium was suscetible to ceftazidime, ciprofloxacin, nalidixic acid, nitrophorantion, amikacin, ceftriaxone, cefotaxime, gentamicin and co-trimoxazole but was resistant to amoxicillin, vancomycin, doxycycline, cephalexin, ampicillin, tetracycline, cephalothin and ceftizoxime. The patient successfully recovered after treatment with antibiotics.